Die veranderende grense van "Transvaal", 1840-1994 (Historia, 2021)
EnglishThe changing borders of the "Transvaal" 1840-1994 During the 150 years of its existence as an administrative unit, Transvaal experienced various important boundary changes and territorial expansions. It occurred especially on the eastern and western borders. While, during the 19th century, the eastern frontier was mainly characterised by territorial expansion - inter alia up to the Lebombo Mountains and the land which was obtained from the Swazi's and the land of the New Republic, the western frontier experienced by times even the loss of territory. During the 20th century, however, this trend was to a large degree reversed.  AfrikaansTransvaal het in die 150 jaar van sy bestaan as administratiewe eenheid verskeie belangrike grensaanpassings en gebiedsuitbreidings ondergaan. Dit het veral aan die oosgrens en wesgrens voorgekom. Terwyl die oosgrens gedurende die 19de eeu hoofsaaklik deur gebiedsuitbreiding gekenmerk is - onder meer uitbreiding tot aan die Lebomboberge, grondgebied van die Swazies verkry en die gebied van die Nuwe Republiek, is aan die wesgrens by tye selfs gebiedsverlies ervaar. Gedurende die loop van die 20ste eeu is dié tendens egter in 'n groot mate omgekeer.
Keywords: J.S Bergh; Transvaal; Lebombo Mountains; noordelike provinsies; Suid-Afrika; Historia; Vaalrivier; A.H. Potgieter; Khumalo Ndebele; Mzilikazi; Pienaarsrivier